Ce-Y co-substituted strontium nanohexaferrites: AC susceptibility and Mossbauer studies. Issue 11 (1st August 2018) - Almessiere, M.A.; Slimani, Y.; El Sayed, H.S.; Baykal, A.
Abstract: Ce-Y co-substituted SrFe12 O19, SrYx Cex Fe12–2x O19 (0.0 ≤ x ≤ 0.5), nanohexaferrites were synthesized via citrate sol-gel combustion route. X–ray diffractometry (XRD), Scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FT-IR), Energy dispersive spectroscope (EDXS) and Elemental mapping were used to study the structure, composition and morphology of the products. Examination through XRD confirms the formation of a pure M phase for all products. Hexagonal plate-like morphology was observed for all samples. EDX and elemental mapping analyses also validated the absence of impurity in the products. The variations in the values of line width, hyperfine magnetic field, quadrupole splitting and isomer shift on Ce and Y substitutions have been investigated through the data of 57 Fe Mossbauer spectroscopy. The Mossbauer study indicated that Ce 3+ and Y 3+ ions are preferentially entering the 4f2 and 2b sites, respectively. The AC magnetic susceptibility experiments show dependency of the magnetic responses with applied frequency, revealing strongly magnetic interactions between the nano-sized particles. Moreover, it is explored that the magnetic interactions are strengthened in substituted nanohexaferrites. This is owed to the replacement of Fe 3+ ions by both Ce 3+ and Y 3+ ions.